2022
DOI: 10.3389/fenrg.2022.910565
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regional Carbon Emission Decoupling Coupling in China Based on ArcGIS Analysis-Empirical Evidence From Urban-Rural Integration in Fujian Province

Abstract: China’s ambitious measures for developing a low-carbon economy led to the “double carbon” target initiation. Under this national goal, reaching peak carbon emissions by 2030 is desired. This should not come at the cost of economic growth; which means carbon emissions can be reduced while economic growth can be achieved simultaneously. To realise this strategic reform, the first pilot ecological civilisation zone in Fujian Province of China was initiated; its outcome is set to be the responsible case for such i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Coupling coordination is the basic principle of sustainable development, and its core connotation emphasizes sustainable and synergy development [30]. Existing studies showed that carbon emissions have a strong interaction with socio-economic development, eco-environment, technological innovation, opening-up, and regional coordination [31,32]. Incorporating carbon emissions into high-quality development systems has a realistic basis.…”
Section: The Study Of Coupling Coordinated Degreementioning
confidence: 99%
“…Coupling coordination is the basic principle of sustainable development, and its core connotation emphasizes sustainable and synergy development [30]. Existing studies showed that carbon emissions have a strong interaction with socio-economic development, eco-environment, technological innovation, opening-up, and regional coordination [31,32]. Incorporating carbon emissions into high-quality development systems has a realistic basis.…”
Section: The Study Of Coupling Coordinated Degreementioning
confidence: 99%